CYBER RESEARCH MENTORING IN SCIENCE IN PHILIPPINE PRIVATE UNIVERSITIES: LEVERAGING ONLINE COLLABORATION TECHNOLOGIES AND OFFSHORE-BASED ALUMNI - Jallorina, Michael Paul A.; Culaba, Ivan B.; Alarcon, Minella; Simpas, James; Aranas, Erika B.; Dingel, Benjamin B. (European Scientific Journal, ESJ, 2014)
The paper discusses an innovative, low-cost, and result-oriented approach to science research mentoring for graduate students and/or junior researchers in Philippine private universities. This so-called Cyber Research Mentoring in Science (CRMS) program has three unique features. First, it leverages offshore-based alumni who are active in science and technology research to be mentors. Second, it utilizes free or inexpensive online collaboration technologies as platforms to bridge the physical gap and to provide virtual presence of the mentors. Third, it requires that all activities lead to journal publications. We evaluate the required collaborative technologies from the perspective of students and mentors, offer best practices as well as critical evaluation, and identify other structural/institutional mechanisms and supports to enhance the success of the program across a range of activities. The last section suggests new avenues for future research.